2005
DOI: 10.1103/physrevb.72.144401
|View full text |Cite
|
Sign up to set email alerts
|

Multipole ordering inf-electron systems on the basis of ajjcoupling scheme

Abstract: We investigate microscopic aspects of multipole ordering in f -electron systems with emphasis on the effect of lattice structure. For the purpose, first we construct f -electron models on three kinds of lattices, simple cubic (sc), bcc, and fcc, by including f -electron hopping through (f f σ) bonding in a tight-binding approximation on the basis of a j-j coupling scheme. Then, an effective model is derived in the strong-coupling limit for each lattice structure with the use of second-order perturbation theory… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2006
2006
2021
2021

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 35 publications
(8 citation statements)
references
References 51 publications
0
8
0
Order By: Relevance
“…There is a multitude of possible high-rank odd order parameters realizable within the = 9/2 ground-state multiplet of Np 4+ ( = 3, 5, 7; i.e., octupolar, triakontadipolar, etc.). A lot of effort has been directed over the last two decades ( 21 , 23 , 24 , 26 29 ) to identify a possible primary order able to reconcile various experimental facts. In particular, assumption of a triakontadipolar antiferromagnetic (AF) 3 order of the symmetry was shown ( 24 , 25 , 30 ) to lead to the best agreement with X-ray scattering and inelastic neutron scattering (INS) spectra.…”
mentioning
confidence: 99%
“…There is a multitude of possible high-rank odd order parameters realizable within the = 9/2 ground-state multiplet of Np 4+ ( = 3, 5, 7; i.e., octupolar, triakontadipolar, etc.). A lot of effort has been directed over the last two decades ( 21 , 23 , 24 , 26 29 ) to identify a possible primary order able to reconcile various experimental facts. In particular, assumption of a triakontadipolar antiferromagnetic (AF) 3 order of the symmetry was shown ( 24 , 25 , 30 ) to lead to the best agreement with X-ray scattering and inelastic neutron scattering (INS) spectra.…”
mentioning
confidence: 99%
“…In fact, the octupole ordering has been strongly suggested by 17 O-NMR experiment [13] and also by inelastic neutron scattering study [14]. As for the microscopic origin of such higher-order multipole ordering, it has been shown that octupole order is stabilized by the orbitaldependent superexchange interaction, and obtained by the second-order perturbation of 5f electron hopping in the Г 8 degenerate Hubbard model on a fcc lattice [15][16][17]. Recently, significant contribution of dotriacontapole moment has been also pointed out [18,19].…”
Section: Introductionmentioning
confidence: 92%
“…The spin-orbit coupling splits the energy levels into a higher-energy j eff = 1 2 doublet and the low-lying j eff = 3 2 quadruplet [9]. Alternatively, we may consider rare earth ions which have a quartet ground state in an octahedral crystal field [25,26].…”
Section: A Symmetry Considerationsmentioning
confidence: 99%
“…The higher value of j eff allows for multipolar interactions which can promote hidden multipolar orders or even quantum spin-orbital liquid phases [19][20][21][22][23]. Multipolar interactions also play an important role in rare-earth systems [24][25][26][27][28], where electrons in the fshell are much more localized and have stronger spinorbit coupling than d electrons in transition metal compounds. Indeed, rare-earth magnets analogous to j eff = 1 2 Kitaev materials have been proposed recently [29][30][31].…”
Section: Introductionmentioning
confidence: 99%